The Relationship of Residential Environment with The Risk of Leptospirosis in Sleman Regency - Maya Sofiyani; M Imron Mawardi; P Sigit Purnomo; Hariza Adnani (Journal of Health Science and Prevention, 2017)
The effort of leptospirosis prevention in Sleman currently only limited to counseling and treatment of the patient, while the patient search, ways of transmission of leptospirosis from rats to humans, have never implemented in an integrated manner. The study aimed to investigated the relationship between the environmental residential condition with the risk of leptospirosis in Sleman Regency. The research used a survey method Ã‚ with case control study design. The results showed that environmental factors, which are not proved to have a relationship with the risk of leptospirosis were residential condition ({p=0,108} OR=3,818 {95%CI:0,922Ã¢â‚¬â€œ15,811}), the trash bin condition ({p=1,000} OR=1,138 {95%CI:0,420Ã¢â‚¬â€œ3,081}) and the sewer condition ({p=0,415} OR=0,551 {95%CI:0,187Ã¢â‚¬â€œ1,624}). Environmental factors that associated with the risk of leptospirosis was the presence of rats ({p=0,001} OR=13,594 {95%CI:2,754Ã¢â‚¬â€œ67,107}). The effort should be made in order to prevent the increasement of Leptospirosis cases by sanitation improvement and avoiding direct contact with rats as well as it litter. The Government should be pay more attention in the vector control programs, especially in leptospirosis prone areas so the prevention effort to be able run effectively and efficiently.